Kinetics of antibody responses to PfRH5-complex antigens in Ghanaian children with Plasmodium falciparum malaria - Partey, F; Castberg, F; Sarbah, E; Silk, S; Awandare, G; Draper, S; Opoku, N; Kweku, M; Ofori, M; Hviid, L; Barfod, L (Public Library of Science, 2018)
Plasmodium falciparum PfRH5 protein binds Ripr, CyRPA and Pf113 to form a complex that is essential for merozoite invasion of erythrocytes. The inter-genomic conservation of the PfRH5 complex proteins makes them attractive blood stage vaccine candidates. However, little is known about how antibodies to PfRH5, CyRPA and Pf113 are acquired and maintained in naturally exposed populations, and the role of PfRH5 complex proteins in naturally acquired immunity. To provide such data, we studied 206 Ghanaian children between the ages of 1-12 years, who were symptomatic, asymptomatic or aparasitemic and healthy. Plasma levels of antigen-specific IgG and IgG subclasses were measured by ELISA at several time points during acute disease and convalescence. On the day of admission with acute P. falciparum malaria, the prevalence of antibodies to PfRH5-complex proteins was low compared to other merozoite antigens (EBA175, GLURP-R0 and GLURP-R2). At convalescence, the levels of RH5-complex-specific IgG were reduced, with the decay of PfRH5-specific IgG being slower than the decay of IgG specific for CyRPA and Pf113. No correlation between IgG levels and protection against P. falciparum malaria was observed for any of the PfRH5 complex proteins. From this we conclude that specific IgG was induced against proteins from the PfRH5-complex during acute P. falciparum malaria, but the prevalence was low and the IgG levels decayed rapidly after treatment. These data indicate that the levels of IgG specific for PfRH5-complex proteins in natural infections in Ghanaian children were markers of recent exposure only.